2D animations in learning the operating system concepts: development & evaluation / Adeline Engkamat ... [et al.] - Engkamat, Adeline; Sarkawi, Adib; Bujang Khedif, Lenny Yusrina (2010)
This research investigated the difficulties faced by students when they are taught subjects that involved processes and abstract theoretical concepts, such as Operating Systenn Concepts. Based on the interview conducted in UiTM Sarawak, it shows that students are not satisfied with the manual teaching methods. Students also have troubles in understanding and visualizing the procesges and abstract theoretical concepts. Consequently, there is a need to enhance the manual teaching methods to achieve the teaching and learning objectives. Animations can be seen as one of the approach to satisfy this need Therefore, this research is done to evaluate the users' satisfaction towards 2D animations in the multimedia application for learning Memory Management topic in Operating System Concepts. A multimedia application with 2D animations is used by the students